Pertumbuhan Bawang Merah (Allium cepa var ascalonicum L.) pada Kultur Hidroponik Sistem Sumbu (Wick) dengan Konsentrasi Pupuk ABmix Berbeda - I Made Subrata; Ni Putu Purnamaningsih (Emasains : Jurnal Edukasi Matematika dan Sains, 2018)
This study aims to determine the growth of onion (Allium cepavarascalonicum L.) due to the administration of AB fertilizer mix with different concentrations in the wick system hydroponic culture and optimal concentration for the growth of onion plants. This research is classified as experimental research. The study design consisted of one control group and 4 treatment groups with 4 replications per group. Each treatment was P0 (without ABmix fertilizer), P1 (ABmix fertilizer 10%), P2 (ABmix fertilizer 20%), P3 (ABmix fertilizer 30%), and P4 (ABmix fertilizer 40%). The population of this research is the seed of onion with a total of 400 tubers. A sample of 300 tubers was taken by random sampling technique. Data collected is data about the wet weight of shallots which include leaves, disc tubers and roots. The data obtained were analyzed by one-way ANOVA with the F test, a significance level of 5%, followed by an average difference test with the BNT test. The results showed that there were differences in onion growth at different ABmix fertilizer concentrations. The optimal fertilizer concentration for the growth of onion is a concentration of 30% (P3). The BNT test showed that the difference in concentration between treatments did not show a significant difference in growth. A very significant difference in growth occurred between the control group and all treatments.